The effect of limited tax loss carryforwards on corporate investment - Hillmann, Lisa; Jacob, Martin (Journal of Accounting and Economics, 2025)
This paper examines the corporate investment effect of a time limit on the use of net operating losses (NOLs). We predict that when countries limit the use of NOLs to a few years instead of allowing indefinite use, managers of loss-making firms have an incentive to increase investments to utilize NOLs before they expire. Using exogenous shocks to profitability from two earthquakes in Italy and variation in the tax treatment of NOLs over time, we find support for this prediction: when the use of NOLs is time-restricted, firms facing losses increase investment. Moreover, this effect is more significant for firms with shorter investment horizons and those in more profitable industries. We provide external validity for this finding using a large panel of firms from European Union countries exploiting variation in tax regimes. These results indicate that restricting loss offsets can increase investments of loss-making firms.